PERBUATAN ASUSILA (STUDI KASUS NAPI DI LAPAS KELAS 1 MAKASSAR) - Muh Aidil Sudarmono R; Abdul Wahab; Dzata Bahjah; Mulyasti Andasari; Syarfina Arfani Guslob (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the various forms of immoral conduct and identify the contributing factors behind such behavior among inmates at the Class I Correctional Facility in Makassar. The research is prompted by the growing incidence of immoral acts within society, as reflected in the number of individuals currently incarcerated at the facility for such offenses. Employing a qualitative research approach, data were collected through observation, in-depth interviews, and document analysis. The subjects of this study consist of inmates convicted of offenses categorized as immoral acts. The findings reveal that the primary forms of immoral behavior include sexual intercourse, acts of indecency, and rape. Furthermore, the underlying causes of such conduct are classified into internal and external factors. Internal factors encompass a lack of religious and moral foundation, as well as emotional and psychological instability. External factors include romantic relationships, familial disapproval, and negative influences from the surrounding social environment. This study underscores the need for a comprehensive understanding of the multifaceted nature of immoral behavior to inform prevention strategies and rehabilitative efforts within correctional institutions.